2002
DOI: 10.1080/02701367.2002.10609025
|View full text |Cite
|
Sign up to set email alerts
|

Injury Rehabilitation: A Goal-Setting Intervention Study

Abstract: The study examined the effects of a 5-week goal-setting intervention on athletes' rehabilitation adherence, self-efficacy, treatment efficacy, and the psychological response variables: dispirited and reorganization. Participants were matched across six variables and randomly assigned to one of three groups: goal-setting intervention, social support control, and control. The results confirmed some of the hypothesized effects of the goal-setting intervention: (a) athlete self-report of adherence showed the goal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 40 publications
4
87
1
1
Order By: Relevance
“…Nevertheless, these findings need to be replicated using a larger sample size before definitive conclusions can be drawn. These findings are in line with those of Evans and Hardy [16] who investigated the use of goal setting as a form of psychological-based intervention for injured athletes. Whereas Evans and Hardy [16] only reported significant effects for time with respect to psychological responses to sport injury, this pilot study demonstrated medium-to-large, albeit non-significant interaction effects for a number of these responses in favour of the experimental group.…”
Section: Psychological Responses To Sport Injurysupporting
confidence: 80%
See 2 more Smart Citations
“…Nevertheless, these findings need to be replicated using a larger sample size before definitive conclusions can be drawn. These findings are in line with those of Evans and Hardy [16] who investigated the use of goal setting as a form of psychological-based intervention for injured athletes. Whereas Evans and Hardy [16] only reported significant effects for time with respect to psychological responses to sport injury, this pilot study demonstrated medium-to-large, albeit non-significant interaction effects for a number of these responses in favour of the experimental group.…”
Section: Psychological Responses To Sport Injurysupporting
confidence: 80%
“…These findings are in line with those of Evans and Hardy [16] who investigated the use of goal setting as a form of psychological-based intervention for injured athletes. Whereas Evans and Hardy [16] only reported significant effects for time with respect to psychological responses to sport injury, this pilot study demonstrated medium-to-large, albeit non-significant interaction effects for a number of these responses in favour of the experimental group. Our findings are also congruent with previous research, which has indicated the beneficial effects of HRV BFB training on stress, anxiety, negative effect, and mood disturbances in sport and clinical settings alike [25,27,28,40].…”
Section: Psychological Responses To Sport Injurysupporting
confidence: 80%
See 1 more Smart Citation
“…Flint 35 reported that 10 athletes recovering from anterior cruciate ligament (ACL) reconstruction who observed peers involved in rehabilitation from the same injury and surgery had increased self-efficacy, self-confidence, and adherence to rehabilitation. Evans and Hardy 36 reported that a goal setting group had higher levels of selfefficacy and they also had the higher mean adherence score, although not significantly different from the control group. Studies have shown that a specific belief that goal setting will assist recovery has been shown to positively influence home and clinic-based adherence in several studies.…”
Section: Personal Factorsmentioning
confidence: 99%
“…Goal setting has been used in sport settings to enhance performance, perceptions of success, and self-efficacy (39,40,41), and also as been recommended for use within injury rehabilitation (42,15,43). Realistically achievable goals create positive expectations and beliefs about goal attainment, thereby enhancing motivation and adherence to the rehabilitation programme (27).…”
Section: Using Short-term Goalsmentioning
confidence: 99%